Lift up your voice like a trumpet : white clergy and the civil rights and antiwar movements, 1954-1973 - Friedland, Michael B. (Chapel Hill : University of North Carolina Press, 1998)
When the Supreme Court declared in 1954 that segregated schools were unconstitutional, the highest echelons of American religious organizations enthusiastically supported the ruling. Many white southern clergy, however, were outspoken in their defense of segregation, and even those who supported integration were wary of risking their positions. Those who did so found themselves abandoned by friends, attacked by white supremacists, and often driven from their communities. Michael Friedland offers a collective biography of several southern and nationally known white religious leaders - including William Sloane Coffin Jr., Daniel and Philip Berrigan, Abraham Joshua Heschel, Eugene Carson Blake, Robert McAfee Brown, and Will D. Campbell - who did step forward to join the major social protest movements of the mid-twentieth century, lending their support first to the civil rights movement and later to protests over American involvement in Vietnam.
Chapter 1 Prophets Without Honor: The Travails of the Southern Clergy, 1954-1960 18 -- Chapter 2 Going South: Northern Clergy and Direction-Action Protests, 1960-1962 49 -- Chapter 3 The Call to Battle: The Churches and Synagogues Enter the Civil Rights Struggle, 1963 70 -- Chapter 4 Bringing Good News to the Oppressed: Clerical Organization in the North South, 1964 93 -- Chapter 5 Flood Tide: Bearing Witness in Alabama, 1965 113 -- Chapter 6 Going Against the Grain: Clergy and Antiwar Movement, 1963-1965 g140 -- Chapter 7 A Voice for Moderation: Clergy and the Antiwar Movement, 1966-1967 164 -- Chapter 8 The Escalation of Dissent: The Antiwar Movement, 1967-1968 189 -- Chapter 9 The Costly Peace: The Antiwar Movement, 1968-1973 213 -- Epilogue 237.
Based on the author's thesis (doctoral)--Boston College, 1993.
Includes bibliographical references (pages 287-303) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Clergy -- Political activity -- United States -- History -- 20th century; Civil rights workers -- United States -- History -- 20th century; Vietnam War, 1961-1975 -- Protest movements -- United States -- History; Whites -- United States -- Politics and government; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Civil rights workers; Clergy -- Political activity; Protest movements; Whites -- Politics and government; United States; Geestelijkheid; Protestbewegingen; 1900-1999; Electronic books; History; Electronic books